α-Anti Subgroup Fuzzy - Nelva Riza, Nelva (Jurnal Pustaka Cendekia Pendidikan, 2023)
A  fuzzy set over a set X is a function of  x to a closed interval [0,1] and is a generalization of a strict set. In other words, a strict set is aspecial case of a fuzzy set, so that the properties of a spring set can definitely be expressed as a special case of a fuzzy set. Information collection method used is the study of literature. By proving the properties of   is the anti fuzzy subgroup of group G.